Evaluation of the Resistance of Some Maize Varieties to Rot Diseases Caused by Different Strains of Fusarium verticillioides (Sacc.) Nirenberg - Akanmu, Akinlolu Olalekan; Sobowale, Ayodele Adegboyega; Odebode, Adegboyega Christopher; Babalola, Olubukola Oluranti (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2025)
Maize ear rot, caused by Fusarium verticillioides, is a significant concern due to its impact on grain contamination and yield reduction. The virulence of this pathogen varies markedly among different strains. This study aimed to assess the pathogenicity of ten F. verticillioides strains; EKT 06, AKR 05, IBD 06, ILH 03, IGH 06, SAK 03, ERW 06, IGB 06, IJB 02, and ILR 05 across three maize varieties: SWAM-1-SR-Y, DMR LSR Y, and BR 9943-DMR-SR-W. A screen-house pathogenicity test was conducted, arranged in a complete randomized design (CRD) with four replications. Inoculation with standardized spore suspensions was conducted through the silk channel in the 7th week after planting (WAP). Among the strains, AKR 05 exhibited the highest virulence, with ear rot severity of 52.8%, followed by ILR 05 (48.6%), ERW 06 (47.3%), and IBD 06 (46.1%). In contrast, SAK 03 (31.4%) and ILH 03 (37.8%) demonstrated the lowest severity levels. The growth parameters of BR 9943-DMR-SR-W were significantly higher than those of SWAM-1-SR-Y and DMR-LSR-Y. The BR 9943-DMR-SR-W variety showed the greatest resistance to the fungal strains, suggesting it is a promising option for cultivation in environments prone to ear rot. Further field trials are necessary to validate these findings.